Pengembangan Aplikasi Rekam Medis Elektronik (RME) Berbasis Web untuk Optimalisasi Pencatatan Data Pasien pada Puskesmas Elopada - Asrin Bani Damanuna; Yulius Nahak Tetik; Agustina Purnami Setiawi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
This study aims to develop a web-based Electronic Medical Record (EMR) application to improve the efficiency and accuracy of patient data recording at Elopada Community Health Center. The research adopts a system development approach using the waterfall model, including requirements analysis, system design, implementation, and testing. Data were collected through observation, interviews, and documentation. The developed system was evaluated using Black Box Testing to verify the conformity between input and output without considering internal program structures. The results indicate that the EMR system enhances data processing speed, improves recording accuracy, and facilitates access to patient information. These findings are consistent with prior studies showing that EMR implementation improves the quality and efficiency of clinical documentation . Therefore, the proposed system is considered feasible to support the advancement of digital healthcare services.